PERANCANGAN IKLAN TELEVISI (TV COMMERCIAL) MACARONI ITALIAN STREET RESTO KOTA PADANG - NORIS MAULANA PUTRA, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Macaroni Italian Street Resto is one of the culinary places in Padang City which is located at Bandar Street No. 4 of Padang Barat, Padang City, West Sumatera. Established since April 5, 2016 up to now with that offer food/ beverage taste of italian food with a blend of Indonesian tastes. And has a classic concept building structure that uses materials such as wood and used goods as furniture.Selection of television advertising as the final work aims to produce an effective and efficient promotion design in accordance with the advantages of television advertising, which can reach a broad target. In addition, with this television ads will be able to introduce Macaroni Italian Street Resto as Italian food food taste creations are cheap / affordable by young people in the city of Padang. SWOT is a method used in doing data collection that is through observation, interview, and documentation. Then proceed with data analysis method by using SWOT analysis (strenght, weakness, opportunity, threats). Further concludes data analysis and creative approach (mainstream and supporting media). In making the design of television advertising Macaroni Italian Street Resto in the city of Padang this writer displays verbal and visual messages for audiences who see this promotion. The design of television advertising is made into 2 (two) namely the main media and supporting media. The design of television advertising Macaroni Italian Street Resto this, is expected to create a good positioning. In addition, it is expected to attract the attention of the target audience, especially among young people in the city of Padang considering the media-based audio visual campaign is a very likely media and a big influence in promoting promotion.Keywords: Café /Resto, Television Ads, Macaroni Italian Street Resto